2022
DOI: 10.1155/2022/7357637
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Analysis of Immune Cells for Diagnosis and Prognosis of Cutaneous Melanoma

et al.

Abstract: Tumor infiltration, known to associate with various cancer initiations and progressions, is a promising therapeutic target for aggressive cutaneous melanoma. Then, the relative infiltration of 24 kinds of immune cells in melanoma was assessed by a single sample gene set enrichment analysis (ssGSEA) program from a public database. The multiple machine learning algorithms were applied to evaluate the efficiency of immune cells in diagnosing and predicting the prognosis of melanoma. In comparison with the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Moreover, these authors could develop prognostic models to estimate composite risk score with clinical parameters to predict survival of over three to 5 years in melanoma patients. Patients can then be stratified based on these models into high versus low risk subgroups with different life expectancies (Du et al, 2022). A subsequent study, using machine learning, confirmed the prognostic value of TNM staging and also found that clinicopathological variables such as sex, tumor site, histotype, growth phase, and age, were linked to OS.…”
Section: Artificial Intelligence and Multiparameter Biomarkersmentioning
confidence: 89%
See 1 more Smart Citation
“…Moreover, these authors could develop prognostic models to estimate composite risk score with clinical parameters to predict survival of over three to 5 years in melanoma patients. Patients can then be stratified based on these models into high versus low risk subgroups with different life expectancies (Du et al, 2022). A subsequent study, using machine learning, confirmed the prognostic value of TNM staging and also found that clinicopathological variables such as sex, tumor site, histotype, growth phase, and age, were linked to OS.…”
Section: Artificial Intelligence and Multiparameter Biomarkersmentioning
confidence: 89%
“…This will ultimately enable identification of patients who would likely benefit from adjuvant therapy (Aung et al, 2022). In another study, machine learning contributed to the development of immune diagnostic models to accurately classify melanoma patients from normal patients (Kulkarni et al, 2020;Du et al, 2022). Moreover, these authors could develop prognostic models to estimate composite risk score with clinical parameters to predict survival of over three to 5 years in melanoma patients.…”
Section: Artificial Intelligence and Multiparameter Biomarkersmentioning
confidence: 99%